Archival Theory: much ado about shelving - Roberts, John (2019)
The field of archival theory is not as fertile as Frank Burke, Gregg Kimball, and others suggest. There are two strains to archival theory. One strain is archival but not theoretical, and deals with the practical, how-to, nitty-gritty of archival work; this is the responsibility of archival clinicians. The other is theoretical but not archival and is concerned with historiography; this is an endeavor not for archivists as archivists but for archivists as historians. This leaves very restricted territory indeed for the archival theorist qua archival theorist. Moreover, the calls for developing a body of archival theory may derive less from an objective need for more archival theory than from an emotional need on the part of an archival community seeking greater professional acceptance.